2021
DOI: 10.5688/ajpe8450
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Preceptor Development Needs Assessment to Inform Program Design and Effectiveness

Abstract: Objective. To describe preceptor teaching challenges and preceptor development programming design preferences through a qualitative needs assessment. Methods. In 2018, 148 experiential education stakeholders across North Carolina (eg, preceptors, residency program directors, experiential faculty administrators, and practice site administrators) were invited to participate in 60-minute semi-structured interviews as part of a broad preceptor development needs assessment. Interview questions focused on:(1) precep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 38 publications
(67 reference statements)
2
13
0
Order By: Relevance
“…Inclusive teaching focuses on creating learning environments that enable students to effectively construct knowledge by leveraging student experience, attitude, motivation, confidence, and participation [ 6 , 21 , 22 ]. The findings of our evaluation align with other studies that indicate a desire for more inclusive training and illustrate positive participant perceptions associated with culturally related training [ 8 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Preceptors in our study, for example, indicated that they desired more inclusive training, which aligns with the results of a previous preceptor needs assessment [ 29 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Inclusive teaching focuses on creating learning environments that enable students to effectively construct knowledge by leveraging student experience, attitude, motivation, confidence, and participation [ 6 , 21 , 22 ]. The findings of our evaluation align with other studies that indicate a desire for more inclusive training and illustrate positive participant perceptions associated with culturally related training [ 8 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Preceptors in our study, for example, indicated that they desired more inclusive training, which aligns with the results of a previous preceptor needs assessment [ 29 ].…”
Section: Discussionsupporting
confidence: 87%
“…The findings of our evaluation align with other studies that indicate a desire for more inclusive training and illustrate positive participant perceptions associated with culturally related training [ 8 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Preceptors in our study, for example, indicated that they desired more inclusive training, which aligns with the results of a previous preceptor needs assessment [ 29 ]. Furthermore, creating an atmosphere of emotional well-being and mutual respect results in students feeling comfortable asking questions, expressing their thoughts and feelings, fostering safety, promoting collaboration, and building a sense of community [ 30 , 31 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 87%
“…Although initial preceptor development is critical to training the novice preceptor, continuing education is key in assuring experienced preceptors can keep akin to the latest strategies for teaching (Williams et al, 2021). Beyond that, The Advisory Board (2021) notes that focusing on professional development opportunities that include career planning can help increase retention.…”
Section: Continuing Education With a Career Pathmentioning
confidence: 99%
“…3 Recent literature described one school's preceptor development needs assessment. 4 Preceptors reported wanting the ability to choose preceptor development topics and wanting frequent sessions delivered via various formats including live at the practice location. 4 Despite the importance of preceptor development, the best delivery method for preceptor development has yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…4 Preceptors reported wanting the ability to choose preceptor development topics and wanting frequent sessions delivered via various formats including live at the practice location. 4 Despite the importance of preceptor development, the best delivery method for preceptor development has yet to be identified. 5,6 There are many challenges associated with preceptor development including time constraints, travel for in-person education, cost, lack of interest, and varied topic needs by preceptors.…”
Section: Introductionmentioning
confidence: 99%